Additional findings of Albunea carabus (Linnaeus, 1758) (Decapoda, Anomura, Hippoidea) in Italian waters - Zava, Bruno (Array, 2019)
The first findings of the anomuran Albunea carabus (Linnaeus, 1758) from the southeastern coa-sts of Sicily are documented, improving knowledge on the distribution of this poorly known species around the island and in the Mediterranean Sea. The distribution of records in the whole basin is updated.